Action research to improve students' attitudes towards mobile devices in learning - Salazar Morcuende, Miguel; Martín Cuadrado, Ana María; Valerio Ureña, Gabriel (Journal of Learning Styles, 2021)
Despite their potential, mobile devices are often seen as a distraction in educational institutions. The aim of this research was to determine to what extent the attitude of first grade high school students towards the use of mobile devices in learning can be improved through action research. For this purpose, three phases were carried out: a) diagnosis, b) intervention and c) evaluation. The results revealed that the action research had a positive impact on students' opinions regarding the academic use of mobile devices (70 to 80); practical use of social networks (58 to 72); digital identity (39 to 73) and reflective use of ICT (73 to 77). This leads to the conclusion that the application of action research methodology can be an effective tool for problem solving in education.
Keywords: educational technology, ICT, knowledge society, mobile learning, social research.